Sur la tendance analytique du polonais - Gawełko, Marek (Lingua Posnaniensis, 2010)
There are different studies of the analytic tendency in Polish. However, a further study is required to permit the determination of the place occupied by Polish on the evolutive scale of the type «synthetic → analytic». The objective of the paper is to establish the distance between Polish and the most evoluated Indo-European languages (English and French) from the point of view of analytism. It is probably true that the passage from synthetic (morphological) structures to analytic (syntactic) ones has taken place sooner in Polish than in Czech. But the two of them are much more synthetic than the most synthetic Romance language (Rumanian) and than German, whose synthetic character, in the domain of Germanic languages, is surpassed only by Icelandic.